All Days 2005
DOI: 10.2118/95516-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Sand and Erosion Alarming on Na Kika, Deepwater Gulf of Mexico

Abstract: A pilot test of an integrated sand and erosion alarming process has been implemented in the NaKika field, in the Gulf of Mexico. All wells have sand control completions. Except for one well with a gravel pack completion problem, all the other wells are controlled by a flux limit (SPE Paper 84495). A Microsoft Excel based program was developed to automatically receive daily morning report data, and perform nodal analysis calculations on all of the wells, in order to estimate: mechanical skin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…They tried to show that injection-pressure response depends not only on the instantaneous measurements but also on the whole history of injection. Parallel to works modeled after fracture propagation in water injectors, water hammer caused by fast shut-in of pumping systems was also identified as one of the main causes of sand production and loss of injectivity in weak formations (Tang and Ouyang 2010;Choi and Huang 2011). Despite the immaculate documentation of water-hammer effects in the field (Wang et al 2008) and elegant mathematical models (Han et al 2002) for this phenomenon, the source of attenuation is not well-understood in these models.…”
Section: Channelizationmentioning
confidence: 99%
See 1 more Smart Citation
“…They tried to show that injection-pressure response depends not only on the instantaneous measurements but also on the whole history of injection. Parallel to works modeled after fracture propagation in water injectors, water hammer caused by fast shut-in of pumping systems was also identified as one of the main causes of sand production and loss of injectivity in weak formations (Tang and Ouyang 2010;Choi and Huang 2011). Despite the immaculate documentation of water-hammer effects in the field (Wang et al 2008) and elegant mathematical models (Han et al 2002) for this phenomenon, the source of attenuation is not well-understood in these models.…”
Section: Channelizationmentioning
confidence: 99%
“…A successful water-injection system is essential for optimum field development by increasing oil recovery, maintaining high reservoir pressure, and minimizing the cost of handling the produced water. A number of publications in the last 2 decades have indicated issues including rapid injectivity decline, out-of-zone injection, and limited longevity of injection wells in the deepwater GOM that have plagued many of these developments (Sharma et al 2000;Stein et al 2005). Al-Kindi et al (2008) reported difficulties with water injectors in the Ursa and Princess fields in the GOM.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the regular surveillance such as pressure-transient analysis, nodal analysis, and production testing, the asset is also using BP's flux-based approach (Tiffin et al 2003;Keck et al 2005) along with integrated sand and erosion alarming (Stein et al 2005). The integrated sand and erosion alarming allows the asset engineers to monitor in real time the completion integrity.…”
Section: Na Kika Field Surveillance and Sand Managementmentioning
confidence: 99%
“…Our new methodology helps to quantify the risk and convert it into a safe target rate. This paper will also present case studies of oil and gas wells in the Na Kika asset in DW GOM where this methodology was applied successfully.The well completions are monitored with BP's flux-based approach (Tiffin et al 2003;Stein et al 2005;Keck et al 2005). In all cases, the wells experienced increased skin, causing the engineers to choke back the wells.…”
mentioning
confidence: 99%
See 1 more Smart Citation